Challenges in implementing securitization to deal with bad debts of credit institutions in Vietnam - Trần Đình Vân (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Dealing with bad debts is considered a key task of the economy in general and of the system of Vietnamese credit institutions in the current period. Among many solutions that have been researched and implemented, securitization is considered a solution with many benefits and suitable for the purpose of dealing with bad debts of the credit institution system. This paper does not present all the contents of securitization as well as the role of securitization with dealing with bad debts of credit institutions in Vietnam, but only analyzes the challenges in implementing securitization to deal with bad debts of the credit institution system in Vietnam in the current period.